Government Social Intervention and Job Creation In Nigeria: A Study of Sure-P and N-Power Programmes, 2012- 2018 (Global Journal of Human-Social Science, 2019)
One of the foremost challenges facing the Nigerian state today is the problem of unemployment among Nigerian youths and this problem has contributed to lot of social vices among Nigerian graduates, such as robbery, prostitution, cybercrimes, hoodlums, political thuggery, etc. This paper aims at investigating Government Social Intervention Schemes and Job Creation in Nigeria, with particular emphasis on former President Good luck Ebele Jonathan social intervention program (SURE-P) and President Muhammadu Buhari social intervention program (N-POWER). This is because the high rate of unemployment among Nigerian graduates is now becoming alarming on daily basis. The paper will therefore examine the extent to which these Governments social programmes have created job opportunities among Nigerian graduates, and also to ascertain whether the rate of unemployed graduates has hindered the Government in creation of jobs in Nigeria.
Keywords: government; social intervention; job creation; SURE-P; N-POWER